A Clinical Evaluation of Lipid Profiles and Oxidative Stress Biomarkers in Hypertensive Individuals with Type-2 Diabetes - Mohsin Shafi, Muhammad Nouman, Masud Ali Ansari, Aaisha Qadir, Naveed Lodhi, Misbah Majeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiovascular disease risk is increased in the coexistence of hypertension and type-2 diabetes, at least in part, by dyslipidemia and oxidative stress. This study investigates the interrelationship between lipid profiles and oxidative stress biomarkers in hypertensive individuals with type-2 diabetes in Pakistan. Methods: The study involved n=120 participants, 80 of whom were hypertensive diabetic patients, and 40 matched age and sex, which were performed as a cross-sectional study. Lipid profiles (total cholesterol, LDL, HDL, and triglycerides) were measured in fasting blood samples by enzymatic colorimetric assay. Plasma malondialdehyde (MDA) levels were quantified and the activities of antioxidant enzymes, superoxide dismutase (SOD), and catalase were determined via spectrophotometric methods to assess oxidative stress. The groups were compared using statistical analysis to find correlations between lipid parameters and oxidative stress markers. Results: The BMI and blood pressure of controls were significantly higher than hypertensive diabetic individuals. Biochemical analyses showed that the study group had markedly increased total cholesterol, LDL cholesterol, triglycerides, and low HDL cholesterol (p < 0.001). In addition, the study group had increased MDA levels and decreased SOD and catalase activities (p < 0.001), indicating increased oxidative stress and impaired antioxidant defense. Conclusion: The results support a key role of dyslipidemia and oxidative stress in hypertensive type 2 diabetic subjects and contribute to their apparent increased cardiovascular risk. These results underscore the importance of integrated management strategies aimed at lipid abnormalities and oxidative stress to improve cardiovascular outcomes in a high-risk population. Keywords: Hypertension, Type-2 Diabetes, Dyslipidemia, Oxidative Stress, Malondialdehyde, Antioxidant Enzymes, Cardiovascular Risk, Pakistan